Impact of the 2016 Kumamoto earthquake on patients with nephrogenic diabetes insipidus and preparations for the future. Issue 2 (30th December 2020) - Tamura, Hiroshi; Nagata, Hiroko; Furuie, Keishiro; Kuraoka, Shohei; Hidaka, Yuko; Nakazato, Hitoshi
Abstract: Patients with nephrogenic diabetes insipidus should establish a support network system by contacting the government to ensure that water can be preferentially obtained in the event of a disaster and create and carry a medical alert card. Abstract : Patients with nephrogenic diabetes insipidus should establish a support network system by contacting the government to ensure that water can be preferentially obtained in the event of a disaster and create and carry a medical alert card.